Taxonomic implications of morphological complexity within the testate amoeba genus Corythion from the Antarctic Peninsula - T. P. Roland; M. J. Amesbury; Dave Wilkinson; D. J. Charman; P. Convey; D. A. Hodgson; J. Royles; S. Clauss; E. Volcker (2017)
Precise and sufficiently detailed morphological taxonomy is vital in biology, for example in the accurate interpretation of ecological and palaeoecological datasets, especially in polar regions, where biodiversity is poor. Testate amoebae on the Antarctic Peninsula (AP) are well-documented and variations in their population size have recently been interpreted as a proxy for microbial productivity changes in response to recent regional climate change. AP testate amoeba assemblages are dominated by a small number of globally ubiquitous taxa. We examine morphological variation in Corythion spp. across the AP, finding clear evidence supporting the presence of two morphospecies. Corythion constricta (Certes 1889) was identified on the AP for the first time and has potentially been previously misidentified. Furthermore, a southerly trend of decreasing average test size in Corythion dubium (TarÃ¡nek 1881) along the AP suggests adaptive polymorphism, although the precise drivers of this remain unclear, with analysis hindered by limited environmental data. Further work into morphological variation in Corythion is needed elsewhere, alongside molecular analyses, to evaluate the potential for (pseudo)cryptic diversity within the genus. We advocate a parsimonious taxonomical approach that recognises genetic diversity but also examines and develops accurate morphological divisions and descriptions suitable for light microscopy-based ecological and palaeoecological studies. Â© 2017 The Author(s)